The patient-reported impact of scars measure: development and validation - Brown, Benjamin C; McKenna, Stephen P; Solomon, Mattea; Wilburn, Jeanette; McGrouther, Duncan A; Bayat, Ardeshir (Plastic and reconstructive surgery (1963), 2010)
Skin scars have a unique impact on patients' lives. Quantification with disease-specific patient-reported outcome measures is essential for assessing disease severity. This study aimed to develop and validate the first scar-specific patient-reported outcome measure. Instrument content was derived from qualitative interviews with scar patients. Quotes were identified from transcripts for use as instrument items. This draft measure was field tested in cognitive debriefing interviews. The final instrument was determined using Rasch analysis in a large-scale validation survey. Five hundred sixty-seven potential items were extracted from interviews (n = 34 patients; 24 women; mean age, 35.7 years). Patients primarily reported physical symptoms and impacts on quality of life. Consequently, a symptom scale (16 items) and quality-of-life scale (36 items) were created. Cognitive debriefing (n = 16 patients; 10 women; mean age, 32.8 years) indicated the draft measure was relevant, clear, and practical. Two quality-of-life items, considered too extreme by patients, were deleted. Ten quality-of-life and three symptom items were removed as a result of the validation survey (n = 103 patients; 69 women; mean age, 35.5 years). Final Rasch analysis confirmed two unidimensional scales (p > 0.05) with good internal consistency (0.85 for the symptom scale and 0.93 for the quality-of-life scale). Reproducibility was adequate for the symptom scale (0.83) and good for the quality-of-life scale (0.89). The Patient-Reported Impact of Scars Measure is the first scientifically rigorous, scar-specific, patient-reported outcome measure. It has two unidimensional scales with good psychometric and scaling properties. It is well accepted by patients and easy to use, and should prove valuable for assessing scar disease severity in clinical trials and in general and specialty clinics.